Effect of vitamin A injection at birth on intramuscular fat development and meat quality in beef cattle - Maciel, Felipe C.; Machado Neto, Otávio R. [UNESP]; Duarte, Marcio S.; Du, Min; Lage, Josiane Fonseca; Teixeira, Priscilla D.; Martins, Cyntia L. [UNESP]; Domingues, Edmilson H.R.; Fogaça, Luiz A. [UNESP]; Ladeira, Marcio M. (Elsevier, 2022)
This study aimed to evaluate intramuscular fat and expression of genes in the muscle of Montana × Nellore treated with vitamin A at birth. We hypothesized that an injection of vitamin A after birth would increase marbling by increasing the expression of angiogenic, adipogenic, and lipogenic genes. Animals treated with vitamin A had greater marbling in the longissimus muscle (P = 0.05). The vitamin A treatment increased the expression of VEGFA gene at 40 days of age and at weaning and increased the expression of ZNF423 at weaning and at harvesting (P ≤ 0.03). The expression of WNT was higher (P = 0.01) at 40 days of age and at weaning in the animals treated with vitamin A. Vitamin A also increased the expression of SREBF1 at 40 days of age and at weaning (P ≤ 0.05). Therefore, the administration of vitamin A to cattle at birth could be a way to increase carcass marbling without affecting the performance of the animals.
Keywords: Gene expression; Marbling; Neonatal programming; Retinoic acid